Site-specific conjugation of antifreeze proteins onto polymer-stabilized nanoparticles. Issue 23 (31st January 2019) - Wilkins, Laura E.; Hasan, Muhammad; Fayter, Alice E. R.; Biggs, Caroline; Walker, Marc; Gibson, Matthew I.
Abstract : Antifreeze proteins are site-specifically conjugated onto polymer-stabilised gold nanoparticles, resulting in hybrid materials capable of modulating ice growth processes. Abstract : Antifreeze proteins (AFPs) have many potential applications, ranging from cryobiology to aerospace, if they can be incorporated into materials. Here, a range of engineered AFP mutants were prepared and site-specifically conjugated onto RAFT polymer-stabilized gold nanoparticles to generate new hybrid multivalent ice growth inhibitors. Only the SNAP-tagged AFPs lead to potent 'antifreeze' active nanomaterials with His-Tag capture resulting in no activity, showing the mode of conjugation is essential. This versatile strategy will enable the development of multivalent AFPs for translational and fundamental studies.